2021
DOI: 10.3390/app11114923
|View full text |Cite
|
Sign up to set email alerts
|

Streptomyces Isolates from the Soil of an Ancient Irish Cure Site, Capable of Inhibiting Multi-Resistant Bacteria and Yeasts

Abstract: Traditional Irish medicines are often intertwined with ritual and spirituality, making it difficult to substantiate the validity of their claims. In this manuscript, we use molecular and microscopic techniques to investigate some microorganisms that might be responsible for the reputed healing properties of an ancient Irish soil cure known as the Blessed clay from a site in Boho in the West Fermanagh Scarplands. We previously reported the isolation of an antibiotic producing bacteria from this soil. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In a recent study conducted by Quinn et al . [156] it was observed that Streptomyces strains isolated from soil possess the ability to combat multi-resistant Staphylococcus aureus and Pseudomonas aeruginosa infections.…”
Section: Streptomyces As a Source Of Antibioticsmentioning
confidence: 99%
“…In a recent study conducted by Quinn et al . [156] it was observed that Streptomyces strains isolated from soil possess the ability to combat multi-resistant Staphylococcus aureus and Pseudomonas aeruginosa infections.…”
Section: Streptomyces As a Source Of Antibioticsmentioning
confidence: 99%
“…A wide range of human infections are linked with this bacteria, such as skin infections, osteomyelitis, fulminant eye infections, endophthalmitis, and sever systematic diseases. 2 Many studies demonstrated that Bacillus species are susceptible to penicillin and cephalosporin with the exception of B. cereus. 3,5 Whereas the most effective bactericidal synergy drugs were clindamycin-gentamicin combination against B.cereus infections.…”
Section: Research Articlementioning
confidence: 99%
“…Earlier studies showed the genome size was ranged from 5.1-6.25 megabases. 1,2 There are many related species with B. cereus, such as B. anthracis, B.mycoides, B. thuringiensis, B. pseudomycoides, B. weihenstephanensis, and some new identified related species. 2 So far, the most clinically significant isolates were B. anthrax, B.cereus, B. megaterium, B. polymyxa, B. pumilus, B. subtilis, and B. amyloliquifaciens that cause of local infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Streptomyces represent a significant source of bioactive natural products (NPs), accounting for 39% of all microbial metabolites [1]. NPs isolated from Streptomyces are diverse and include antibiotic, anticancer, antioxidant, and other bioactivities [2][3][4]. Since extreme environments form severe habitats, they may give rise to unique metabolic pathways in microorganisms.…”
Section: Introductionmentioning
confidence: 99%